International remittance inflows and import spending in Nigeria - Sanusi, Gbenga Peter; Oderinde, Oladele L. (Wpływ międzynarodowych przekazów i wydatki importowe w Nigerii, 2020)
This study examined the historical trends of remittances and import spending in Nigeria to determine the possible aftermaths of COVID-19 pandemic. Time series data for the period 1977- -2019 was used in a VAR model. Result indicates that a unit shock on remittances accounts for about 28% variation in import demand in the second period. Migrant’s remittances and GDP per capita show a weak endogenous relationship. Remittances tend to be stable and not affected by the exchange rate. Thus, import demand may not reduce significantly due to fall in remittances as a consequence of COVID-19. Therefore, improved industrial expansion in the production of goods and services are essential in curtailing aggregate import demand
Financial Sciences. Nauki o Finansach, 2020, vol. 25, no. 2-3, s. 55-79
Keywords: international remittance; migrants; import spending; VAR model; Nigeria; przekazy zagraniczne; migranci; wydatki importowe; model VAR